Clinical and social aspects of dysmenorrhea development - O. P. Dolhikh; M. I. Romanenko; D. H. Ivanchenko; K. V. Aleksandrova; N. M. Polishchuk (Zaporozhye State Medical University, 2019)
Modern antibiotics and synthetic antimicrobial agents play a leading role in the treatment of bacterial infections. Despite their effectiveness, they cause a number of side effects, and thus the search for new antimicrobial and antifungal agents is currently one of the problems of pharmaceutical science of current interest. Literary data suggest that xanthine derivatives exhibit activity in relation to some strains of pathogenic microorganisms and fungi. The aim of this work is to develop a method for the synthesis of new derivatives of xanthine-8-aminoalkanoic acids and to study their physical and chemical properties, as well as their antimicrobial and antifungal effects. Materials and methods. The melting point has been determined with the help of an open capillary method with PTP-M device. Elemental analysis has been performed with the help of the instrument Elementar Vario L cube, NMR-spectra have been taken on a spectrometer Bruker SF-400 (operating frequency of 400 MHz, solvent DMSO, internal standard - TMS). Study of antimicrobial and antifungal activity of synthesized compounds has been performed by a two-fold serial dilution method. Standard test strains have been used for the study: Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 25923, Pseudomonas aeruginosa ATCC 27853, Candida albicans ATCC 885-653. Dimethylsulfoxide was used as the solvent of the compounds. Results. The reaction of 8-brom-7-ethylxanthines with an excess of the corresponding aminoalkanoic acid in an aqueous DMF medium in the presence of an equimolar (in relation to the amino acid) amount of baking soda leads to the formation of the corresponding 7-ethylxanthinyl-8-aminoalkanoic acids. Structure of synthesized compounds was definitely proved by 1Н NMR-spectroscopy. Conducting primary screening research of antimicrobial activity of 7-ethylxanthinyl-8-aminoalkanoic acids derivatives, which revealed moderate and weak activity in concentrations 50-100 mcg/ml. Conclusions. A preparative method of synthesis of not described in the literature 7-ethylxanthinyl-8-aminoalkanoic acids is developed. The structure of the synthesized compounds has been proved with the help of data of the 1H NMR spectroscopy. The antimicrobial and antifungal effects of the obtained compounds have been studied. The perspective of xanthine-8-alkanoic acids for the further search of biologically active compounds is shown.